PROMOSI KESEHATAN TENTANG PERSONAL HYGIENE ORGAN REPRODUKSI REMAJA DI SMP KOTA PADANG - Erdanela Setiawati; Amran, Rika; Sjaaf, Fidiariani; Lovprim, Nopeliantesa (Nusantara Hasana Journal, 2026)
Personal hygiene of reproductive organs is an important component in maintaining the cleanliness and health of adolescent reproductive organs. Poor personal hygiene impacts the ease of infection of adolescent reproductive organs. The prevalence of Reproductive Tract Infections (RTIs) is quite high among adolescents in Indonesia and globally. Low knowledge, inappropriate habits, and limited access to health information are contributing factors to this problem. It is important for adolescents to obtain accurate information about the cleanliness and health of reproductive organs and various factors that influence reproductive health. This activity aims to increase adolescent knowledge and awareness regarding the importance of maintaining cleanliness and health of reproductive organs. The activities carried out included educational, interactive and participatory counseling, accompanied by discussions, quizzes, and evaluation using pre-tests and post-tests. The activity was held on Thursday, December 4, 2025 at the SMPN 28 Padang Mosque and attended by 43 junior high school students. Analysis of the pre-test and post-test results showed an increase in the average knowledge score from 15.0 (50%) in the pre-test to 24.9 (83%) in the post-test, with a difference of 9.9 points (33%). participant participation during the activity was quite good and showed high enthusiasm. This health promotion activity proved effective in increasing adolescents’ knowledge and understanding of personal hygiene of reproductive organs with an increase in score from 15.0 points to 24.9 points. It is hoped that the knowledge gained will contribute to the formation of clean and healthy living behaviors in a sustainable manner.